Dari Anonim Kembali ke Anonim - Saptiawan, Itsna Hadi (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2018)
The context of current mass communication in Indonesia, especially on social media, shows news constellations that lead to hoax war and the spread of fake accounts (bots). This study aims to normatively understand the historical role of literature behind the emergence of these anonymous characteristics and the latest patterns presented in the public space. The internet as a communication laboratory is the main subject of content analysis. The results show that social media has the potential to expand and disseminate communication that is more intense and massive when compared to other internet mediums.Keywords: anonymous; hoaxes; communication.